Life's a breach! Ensuring `permanence' in forest carbon sinks under incomplete contract enforcement - Charles Palmer; Markus Ohndorf; Ian A. MacKenzie (ETH Zurich, CER-ETH - Center of Economic Research, 2009)
As carbon sinks, forests play a critical role in helping to mitigate the growing threat from anthropogenic climate change. Forest carbon offsets transacted between GHG emitters in industrialised countries and sellers in developing countries have emerged as a useful climate policy tool. A model is developed that investigates the role of incentives in forestry carbon sequestration contracts. It considers the optimal design of contracts to ensure landowner participation and hence, permanence in forest carbon sinks in a context of uncertain opportunity costs and incomplete contract enforcement. The optimal contract is driven by the quality of the institutional framework in which the contract is executed, in particular, as it relates to contract enforcement. Stronger institutional frameworks tend to distort the seller's effort upwards away from the full enforcement outcome. This also leads to greater amounts of carbon sequestered and higher conditional payments made to the seller. Further, where institutions are strong, there is a case for indexing the payment to the carbon market price if permanence is to be ensured. That is, as the carbon price increases, the payment could be raised and vice versa.
Keywords: K12; Q15; 330; forest carbon offsets; permanence; contract design; incomplete enforcement; CO2-Speicherung; Normbefolgung; Vertragstheorie